PEMAKNAAN TINDAK TUTUR DIREKTIF GURU PENUTUR ASLI DAN NON PENUTUR ASLI DALAM PEMBELAJARAN BAHASA INGGRIS - I Gusti Ayu Vina Widiadnya Putri; I Dewa Ayu Devi Maharani Santika; Komang Dian Puspita Candra (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2019)
This study aims to describe the meaning of the directive illocutionary speech acts used by Native Speakers and Non-Native Speakers in teaching English at the Denpasar Children Center School. The data sources of this study are the utterance of native speaker and non-native speaker. Data obtained by using observation method with uninvolved conversation observation technique and record techniques. Data containing illocutionary speech acts then analyzed descriptively qualitatively based on theories of speech act proposed by Searle (1969) and Leech (1974) about meaning. The results showed that the directive speech acts used by native speakers and non-native speakers were requirements, requestives, questions, prohibitive, permissives and advisories. The meanings of directive speech acts spoken by native speakers and non-native speakers are analyzed from the context of the conversation. The meaning of speech acts for the native speaker tends to be connotative and sometimes contains affective meaning. Whereas the meaning of speech acts of non-native speaker tend to use a combination of connotative, denotative, and affective meanings.